Alfred Dupont Chandler (1918-2007): thoughts on strategy - Cowan, Roberta (2007)
The noted business historian, Alfred Dupont Chandler, Jr., the author of hundreds of journal articles and numerous books, died in May. As a Harvard professor in the 1970s, he revitalized business history, as a career choice for historians, as a serious branch of history and as a source of research that contributed to the fast-moving field of strategic management. This working paper discusses his contribution to strategy and provides a list of his monographs with comments on translations and reprintings.